Effect of Dendrobium Officinale on Radioactive Oral Mucositis of Nasopharyngeal Carcinoma and Changes of Oral Microecology - Jiaying Yang MM; Yuancai Liu MM; He Yao MM; Mengying Sun MM; Yangbo Tong MM; Guanjun Ma MM; Zhuo Chen MD; Xiang Qian MD; Aiqin Zhang MD (Integrative Cancer Therapies)
Objective: To observe the clinical efficacy of Dendrobium officinale in the treatment of radiotherapy-induced oral mucositis in nasopharyngeal carcinoma patients, and to explore its regulating effect on immune function and oral microbiota by comparing immune-related factors and oral microbiota before and after the intervention. Methods: We conducted a randomized double-blinded controlled trial in Zhejiang Cancer Hospital. Sixty patients with nasopharyngeal cancer combined with radiotherapy-induced oral mucositis were randomly divided into a study group and control group, with 30 cases in each group The study group used compound vitamin B12 solution and Dendrobium tea drink, and the control group simply used compound vitamin B12 solution rinse. When the patients developed radiotherapy-induced oral mucositis (at the time of 10F radiotherapy), and after 1 month of Dendrobium treatment (at the end of radiotherapy), the salivary flow rate was measured without stimulation to evaluate the degree of oral mucositis and the clinical efficacy. We also detected the content of EGF in saliva and the content of IL-10 and IL-11 in serum, and analyzed the differences in microbial community structure. All patients consented before enrollment. Results: The salivary flow rate and oral mucosal fraction of the study group after treatment were significantly improved, which was better than that of the control group( P  < .05). The content of IL-10 in the study group after treatment increased significantly compared with that before treatment( P  < .05). There was a significant difference between the oral flora of the study group before and after treatment (Unique OTU counts: 5390 vs 3906), and there was also a difference between the oral flora of the study group and control group after treatment (Unique OTU counts: 5671 vs 5439). After treatment, Erysipelotrichales (Phylum Firmicutes, LDA score = 2.80, P  = .034), Leptotrichiaceae (Fusobacteria,LDA score = 3.38, P  = .030) and Campylobacteraceae (Proteobacteria, LDA score = 3.35, P  = .026) were significantly enriched in the study group. The use of Dendrobium officinale in nasopharyngeal carcinoma patients with radiotherapy-induced oral mucositis showed little difference in microbial diversity and abundance, but there were significant differences among oral bacteria genera. Conclusions: Dendrobium officinale is effective in the treatment of radiotherapy-induced oral mucositis, which may be related to the improvement of salivary gland function and regulation of the oral microenvironment. Dendrobium officinale may reduce the symptoms of radiotherapy-induced oral mucositis by affecting the systemic cellular immune function. It may reduce the secretion of pro-inflammatory factors of the relevant flora by directly changing the oral flora and regulating the oral micro-ecology.